ANEMIA AMONG ADOLESCENT GIRLS: A GLOBAL REVIEW OF PREVALENCE, RISK FACTORS, AND INTERVENTIONS - Fitariani, Selvia; Masruroh; Mawarti, Herin; Nasrudin (Nurse and Holistic Care, 2025)
Background: Anemia remains a significant public health challenge affecting adolescent girls worldwide, particularly in low- and middle-income countries (LMICs). This condition undermines growth, cognitive development, school performance, and reproductive health, with long-term intergenerational consequences. Objective: This systematic review aimed to systematically review the global prevalence, associated risk factors, and intervention strategies targeting anemia among adolescent girls, and to identify research and policy gaps that hinder effective prevention. Design: A systematic review of quantitative and mixed-methods studies conducted between January 2019 and May 2024 was undertaken by the PRISMA guidelines. Data Sources: Five electronic databases (PubMed, Scopus, Web of Science, ScienceDirect, and Google Scholar) were searched using Boolean combinations of keywords such as "anemia," "adolescent girls," "risk factors," and "intervention." Additional records were retrieved from grey literature and manual reference checks. Review Methods: Eligible studies included observational, interventional, and mixed-methods research on adolescent girls aged 10–19 years, with clear reporting of anemia prevalence or related risk factors. Quality appraisal was conducted using the Joanna Briggs Institute (JBI) tools. Thematic synthesis was applied to categorize risk factors and interventions. Results: A total of 12 studies from over 8 countries were included. Anemia prevalence ranged from 25% to 61%, with the highest rates reported in Sub-Saharan Africa and South Asia. Major risk factors included poor dietary diversity, early menarche, menstrual disorders, parasitic infections, and low socioeconomic status. School-based iron and folic acid (IFA) supplementation combined with nutrition education and community engagement showed the most promising results. However, adherence and program sustainability were frequently reported challenges. Conclusion: Anemia among adolescent girls is a multidimensional issue requiring context-specific, multisectoral approaches. Integrating education, supplementation, and culturally adapted interventions can enhance program effectiveness. Future research should focus on long-term outcomes, behavioral drivers, and scalable solutions tailored to the needs of adolescent populations.